Heterologous expression of a thermophilic diacylglycerol acyltransferase triggers triglyceride accumulation in Escherichia coli - Lázaro, Beatriz [UNESP]; Villa, Juan A.; Santín, Omar; Cabezas, Matilde; Milagre, Cintia D.F. [UNESP]; De La Cruz, Fernando; Moncalián, Gabriel (Public Library of Science (PLoS), 2017)
Triglycerides (TAGs), the major storage molecules of metabolic energy and source of fatty acids, are produced as single cell oil by some oleogenic microorganisms. However, these microorganisms require strict culture conditions, show low carbon source flexibilities, lack efficient genetic modification tools and in some cases pose safety concerns. TAGs have essential applications such as behaving as a source for added-value fatty acids or giving rise to the production of biodiesel. Hence, new alternative methods are urgently required for obtaining these oils. In this work we describe TAG accumulation in the industrially appropriate microorganism Escherichia coli expressing the heterologous enzyme tDGAT, a wax ester synthase/triacylglycerol:acylCoA acyltranferase (WS/DGAT). With this purpose, we introduce a codon-optimized gene from the thermophilic actinomycete Thermomonospora curvata coding for a WS/DGAT into different E. coli strains, describe the metabolic effects associated to the expression of this protein and evaluate neutral lipid accumulation. We observe a direct relation between the expression of this WS/DGAT and TAG production within a wide range of culture conditions. More than 30% TAGs were detected within the bacterial neutral lipids in 90 minutes after induction. TAGs were observed to be associated with the hydrophobic enzyme while forming round intracytoplasmic bodies, which could represent a bottleneck for lipid accumulation in E. coli. We detected an increase of almost 3- fold in the monounsaturated fatty acids (MUFA) occurring in the recombinant strains. These MUFA were predominant in the accumulated TAGs achieving 46% of the TAG fatty acids. These results set the basis for further research on the achievement of a suitable method towards the sustainable production of these neutral lipids.